2008
DOI: 10.1007/s10787-008-8021-z
|View full text |Cite
|
Sign up to set email alerts
|

Soy consumption for reduction of menopausal symptoms

Abstract: Consumption of 30 mg/day of soy isoflavones (or at least 15 mg genistein) reduces hot flashes by up to 50 %. This total reduction includes that provided by "the placebo effect". The greatest benefit may be realized when the isoflavone-rich food or supplement is taken in divided doses by subjects who experience at least four hot flashes/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…More recently, evidence suggests that isoflavones may not only have estrogenic effects, but are also antiestrogenic in some mammalian tissues [4]. The preferential binding of isoflavones to estrogen receptor β suggests that they may act as SERMs (selective estrogen receptor modulators) [5]. The majority of soy diet and bone research has been conducted in adult human participants and experimental rodents.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, evidence suggests that isoflavones may not only have estrogenic effects, but are also antiestrogenic in some mammalian tissues [4]. The preferential binding of isoflavones to estrogen receptor β suggests that they may act as SERMs (selective estrogen receptor modulators) [5]. The majority of soy diet and bone research has been conducted in adult human participants and experimental rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in randomized clinical trials, genistein has been shown to reduce hot flashes by 50% [1] . Epidemiological and case-controlled studies in Asian women have reported a negative correlation between breast cancer and the intake of soy products [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…30 So, the current authors' dietary approach is primarily based on epidemiologic data: Asian women on a traditional diet average a 10%-20% incidence of vasomotor symptoms, compared to the 70%-80% incidence in Western countries. 31 There are also suggestions underscoring the difference between whole foods (and whole herbs) versus supplements. For instance, soy is deemed to have heart-healthy benefits, which are often attributed to soy isoflavones.…”
Section: A Basic Approach To Night Sweatsmentioning
confidence: 99%